On Janowski Type Harmonic Meromorphic Functions with respect to Symmetric Point. (27th January 2021) - Khan, Muhammad Ghaffar; Ahmad, Bakhtiar; Darus, Maslina; Mashwani, Wali Khan; Khan, Shahid
Abstract : In this paper, we define a new class of Sakaguchi type-meromorphic harmonic functions in the Janowski domain that are starlike with respect to symmetric point. Furthermore, we investigate some important geometric properties like sufficiency criteria, distortion bound, extreme point theorem, convex combination, and weighted means.